(3cja JcTa GdcPGHs (3deGPG dG jbhd GdfGS GdMbjbI, hcja jecfc Cf JcTa cPHges - (3gGQJdj, LQjLhQis; (3cGQjfT, eGQjGfGs; (3ecJHI LQjQs ((3GdQjGVs (3ecJHI LQjQs, 2006)
(3jbOe dc GdeDdaGf JhLjgG eMOOG YedjG Mhd cjajI cTa GdcPH, hPdc ef NdGd GdYOjO ef GdCeUdI GdhGbYjI (B. (3Sha JTMP gPI GdOQhS egGQGJ GdedGMXI dOjc, ceG CfgG Sha JMSf ef egGQGJc GdTNUjIs
(3eJhGaQ EYGOI GdWHYI GdKGfjI dYGe (B2008 (3HecJHI eUQ GdYGeI (B- (3GdecJHI GdQFjSjIs
(3eJhaQ efg GdWHYI GdGhdi dSfI (B2013 (3ecJHI eUQ GdYGeI (B-- (3aQY GdRGhjI GdMeQGAs
(3gPG GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdEfLdjRjIs
1 2 3 13
Keywords: (3GdcPHs; (3GdebGHdGJ GdTNUjIs